Understanding quality of life in bipolar disorder: associated factors and coping strategies - Alzahrani, Hessah (Frontiers in Psychology, 2024)
Background: Bipolar disorder (BD) is a chronic mental health condition that significantly affects an individual's quality of life (QoL). While previous research has primarily concentrated on the clinical aspects of BD, there is increasing interest in understanding the factors associated with QoL in this population. This cross-sectional study aimed to assess the effects of different coping strategies on the overall QoL of individuals with BD, encompassing the physical, psychological, and social dimensions, while comparing adaptive and maladaptive coping strategies. The study sample included 96 outpatients diagnosed with BD recruited from psychiatric outpatient clinics in Riyadh and Dammam, Saudi Arabia, as well as a broader BD community. Participants completed the World Health Organization Quality of Life Brief questionnaire (WHOQOL-BREF) and Coping Orientation to Problems Experienced (Brief-COPE) questionnaires. Results: The findings indicated that problem-focused coping strategies, such as seeking support and taking direct action to manage stress, were associated with better QoL among individuals with bipolar disorder. In contrast, emotion-focused strategies such as self-blame are linked to lower QoL. Conclusion: These results contribute to the limited research on QoL in BD, particularly in Arab and Saudi societies, and underscore the need for targeted interventions aimed at developing effective coping mechanisms to enhance the well-being of individuals with BD.